Mitochondrial genomes of two parasitic Cuscuta species lack clear evidence of horizontal gene transfer and retain unusually fragmented ccmF C genes - Benjamin M. Anderson (BMC, 2021)
Abstract Background The intimate association between parasitic plants and their hosts favours the exchange of genetic material, potentially leading to horizontal gene transfer (HGT) between plants. With the recent publication of several parasitic plant nuclear genomes, there has been considerable focus on such non-sexual exchange of genes. To enhance the picture on HGT events in a widely distributed parasitic genus, Cuscuta (dodders), we assembled and analyzed the organellar genomes of two recently sequenced species, C. australis and C. campestris, making this the first account of complete mitochondrial genomes (mitogenomes) for this genus. Results The mitogenomes are 265,696 and 275,898 bp in length and contain a typical set of mitochondrial genes, with 10 missing or pseudogenized genes often lost from angiosperm mitogenomes. Each mitogenome also possesses a structurally unusual ccmF C gene, which exhibits splitting of one exon and a shift to trans-splicing of its intron. Based on phylogenetic analysis of mitochondrial genes from across angiosperms and similarity-based searches, there is little to no indication of HGT into the Cuscuta mitogenomes. A few candidate regions for plastome-to-mitogenome transfer were identified, with one suggestive of possible HGT. Conclusions The lack of HGT is surprising given examples from the nuclear genomes, and may be due in part to the relatively small size of the Cuscuta mitogenomes, limiting the capacity to integrate foreign sequences.